2004
DOI: 10.1001/archinte.164.16.1788
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Chronic Kidney Disease With Laboratory Reporting of Estimated Glomerular Filtration Rate and an Educational Program

Abstract: Laboratory reporting of estimated GFR coupled with an educational program markedly improves the recognition of CKD in the primary care setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
90
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(96 citation statements)
references
References 46 publications
5
90
1
Order By: Relevance
“…A third study, which included an educational intervention as well, noted a 4-fold increase in detection rates. 18 Given the small improvements in physician recognition seen with reporting alone, it may have been the educational intervention that improved recognition in this last study. If that is the case, emphasizing estimated GFR may not be enough.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…A third study, which included an educational intervention as well, noted a 4-fold increase in detection rates. 18 Given the small improvements in physician recognition seen with reporting alone, it may have been the educational intervention that improved recognition in this last study. If that is the case, emphasizing estimated GFR may not be enough.…”
Section: Discussionmentioning
confidence: 89%
“…At least 3 studies have assessed the effects of eGFR reporting on clinician recognition and behavior. [17][18][19] Two of these, which included only reporting, found only modest increases in physician recognition. A third study, which included an educational intervention as well, noted a 4-fold increase in detection rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early recognition by PCPs is essential to implement treatments to slow CKD progression. Although previous studies have shown poor recognition of CKD, limitations include data collection in single centers and use of International Classification of Disease (ICD) codes to evaluate documentation, which may underestimate practitioner recognition (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…The use of automatic reporting of estimated GFR (eGFR) is controversial (9,10), and results evaluating its implementation on improving CKD recognition have been variable (5,7,11).…”
Section: Introductionmentioning
confidence: 99%